Pertanggungjawaban Hukum dari Pelaku Usaha dengan Adanya Produk Skincare Beretiket Biru yang Beredar Bebas dan Upaya Penyelesaiannya Ditinjau dari Hukum Positif di Indonesia - Priscilla Junita Setiawan; Pan Lindawaty Suherman Sewu (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2025)
As time goes by, physical appearance has become important in people's lives, due to the increasing interest in facial care products such as cosmetics and skincare. In fact, there is free distribution of skincare with a blue label which should be obtained in consultation with a doctor and is only made into a mixture or should not be used. stock. It is known that one of the examples of materials contained such as hydroquinone and corticosteroids Inappropriate use of these ingredients can trigger dangerous side effects for consumers. Based on regulations, skincare with the blue label should be used on a limited basis and requires a distribution permit. However, in fact there are still many products skincare with blue labels sold freely. Therefore, this journal aims to analyze the legal liability of business actors who distribute skincare with blue labels freely, the impact on consumers and consumer protection, and efforts to resolve disputes. The aim of the analysis is for Indonesia to have clear regulations regarding skincare with a blue label to provide legal certainty to the public or consumers.